Subcellular localization and in vivo identification of the putative movement protein of olive latent virus 2 - Grieco, Francesco; Castellano, Maria Antonietta; Di Sansebastiano, Gian Pietro; Maggipinto, Giovanna; Neuhaus, Jean-Marc; Martelli, Giovanni P (My University, 1999)
The gene encoding the 36.5 kDa ('36K') nonstructural protein located on RNA3 of olive latent virus 2 (OLV-2) was cloned, expressed with the Escherichia coli pGEX-2T system and the purified protein used to raise a polyclonal antiserum. Immunoblot analysis of OLV-2-infected Nicotiana benthamiana plants showed that the 36K protein accumulated in the early stages of infection and was associated with a subcellular fraction enriched in cytoplasmic membranes. In infected cells there were tubular structures, some containing virus-like particles, scattered in the cytoplasm or protruding from or penetrating the cell wall at the plasmodesmata, Immunogold labelling localized the 36K protein in the plasmodesmata of OLV-2-infected cells and showed it to be associated with virus-containing tubules, Leaf trichome cells of N. tabacum plants, transformed with a 36K-green fluorescent protein (GFP) fusion construct, revealed localized fluorescence in the cell walls, possibly due to association of the fusion protein with plasmodesmata, When the same 36K-GFP fusion protein was expressed in N. tabacum protoplasts, long tubular fluorescent structures protruded from the protoplast surface, suggesting that the 36K protein is responsible for tubule induction. The conclusion is drawn that this protein is likely to be the OLV-2 movement protein, mediating cell-to-cell virus movement, and that movement is by a tubule-guided mechanism.
Keywords: COWPEA MOSAIC-VIRUS; CELL-TO-CELL; TRANSGENIC TOBACCO PLANTS; GREEN; FLUORESCENT PROTEIN; TUBULAR STRUCTURES; NUCLEOTIDE-SEQUENCE; FAMILY; BROMOVIRIDAE; NUCLEIC-ACIDS; INSECT CELLS; IN-VIVO